Rhizobium japonicum nitrogenase Fe protein gene (nifH). - Fuhrmann, M (1984)
A 12.1-kilobase PstI fragment from Rhizobium japonicum, which contains homology to both the Klebsiella pneumoniae and the Rhizobium meliloti nifH genes, was cloned into vector pHE3 . The nifH -homologous region was localized on the restriction enzyme cleavage map by Southern blot hybridization experiments. DNA fragments overlapping the R. japonicum nifH gene were subcloned into plasmid vectors to allow the expression of this region in Escherichia coli minicells. The nifH gene product (the polypeptide of the nitrogenase Fe protein) was thus found to have a molecular weight of 33,000. The complete nucleotide sequence of the nifH gene was established, and the amino acid sequence of its gene product was deduced. The reading frame is 882 nucleotides long, corresponding to 294 amino acids which add up to a polypeptide with a molecular weight of 31,525. There was extensive sequence homology with nifH genes or gene products from other nitrogen-fixing bacteria. The transcription initiation site of the R. japonicum nifH gene was found to lie 153 nucleotides upstream from the coding region and was preceded by a characteristic promoter sequence. A potential terminator region was located 13 nucleotides downstream from the coding region.